Unexpected diversity of ratites (Aves, Palaeognathae) in the early Cenozoic of South America: palaeobiogeographical implications. Issue 1 (2nd January 2017) - Agnolin, Federico L.
Abstract : Agnolin, F.L., July 2016. Unexpected diversity of ratites (Aves, Palaeognathae) in the early Cenozoic of South America: palaeobiogeographical implications. Alcheringa 41, xxx–xxx. ISSN 0311-5518. Ratitae is represented in South America exclusively by Rheidae. Recently, the oldest purported fossil rheid, Diogenornis fragilis, was attributed by several authors to various other ratite clades. A new revision of museum fossil specimens from Argentina has resulted in the discovery of several ratite specimens that clearly do not belong to Rheidae, but resemble other clades. The newly identified specimens derive from Paleogene and Miocene strata. The great diversity of non-rheid Patagonian ratites ended via extinction of several groups by the late Miocene, probably owing to enhanced aridity that also favoured the dispersal of arid-adapted rheids. The new specimens described here reinforce the hypothesis that the traditional vicariant biogeographical model, which proposes ratite clades originated exclusively before the breakup of the Gondwana supercontinent, is questionable owing to the unexpected diversity of various ratite clades in South America, and also in Europe and Africa. This might indicate that the history of Ratitae was more complex than previously envisioned. Federico L. Agnolin* [ fedeagnolin@yahoo.com.ar ], Laboratorio de Anatomía Comparada y Evolución de los Vertebrados, Museo Argentino de Ciencias Naturales 'Bernardino Rivadavia', Av. Ángel Gallardo, 470 (1405), Buenos Aires, Argentina. *Also affiliated with: Fundación de Historia Natural 'Félix de Azara', Departamento de Ciencias Naturales y Antropología, Universidad Maimónides, Hidalgo 775 (C1405BDB) Ciudad Autónoma de Buenos Aires, República Argentina.